Pengaruh Comprehensive Stakeholder Pressure dan Good Corporate Governance terhadap Kualitas Sustainability Report - Sriningsih Sriningsih; Indah Fajarini Sri Wahyuningrum (Owner : Riset dan Jurnal Akuntansi, 2022)
ABSTRACT This study aims to analyze the effect of comprehensive stakeholder pressure and good corporate governance (GCG) on sustainability report quality. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019 period. The technique used is purposive sampling, in order to obtain a sample of 138 units of analysis. The data was collected using documentation method. The data was analyzed using descriptive statistical analysis and multiple linear regression analysis with SPSS. The results showed that industries close to consumers, environmentally sensitive industries, and media exposure had a significant positive effect on sustainability report quality. The audit by KAP Big 4 and the effectiveness of the Board of Commissioners have a significant negative effect on sustainability report quality. Meanwhile, investor-oriented industry, employee-oriented industry, creditor pressure, government pressure, and the Audit Committee have no influence on sustainability report quality. Based on the research results, government is expected to be able to clarify regulations regarding the disclosure of the sustainability report and encourage the disclosure of GRI sectoral content in the sustainability report. Further research is expected to use the scoring method to measure the quality of the sustainability report and other proxies to measure the effect of stakeholder pressure on the quality of the sustainability report. Keywords : Sustainability Report Quality; Stakeholder Pressure; Board of Commissioner; Audit Committee.